2015
DOI: 10.5194/amt-8-1043-2015
|View full text |Cite
|
Sign up to set email alerts
|

A new Dobson Umkehr ozone profile retrieval method optimising information content and resolution

Abstract: Abstract. The standard Dobson Umkehr methodology to retrieve coarse-resolution ozone profiles used by the National Oceanographic and Atmospheric Administration uses designated solar zenith angles (SZAs). However, some information may be lost if measurements lie outside the designated SZA range (between 60 • and 90 • ), or do not conform to the fitting technique. Also, while Umkehr measurements can be taken using multiple wavelength pairs (A, C and D), past retrieval methods have focused on a single pair (C). H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Umkehr measurements rely on the fact that the scattering intensity of solar UV (effective scattering height) changes with solar zenith angle (SZA). Since most of the ozone in the atmospheric column is in the stratosphere, the information content of the tropospheric part of the retrieval is limited, and only ~5 0% or less of the information in layer 1 (1000-250 hPa in the standard retrieval) comes from the troposphere (Stone et al, 2015; Text S-9), while the rest of the information comes from the adjacent stratospheric layers.…”
Section: Umkehrmentioning
confidence: 99%
“…Umkehr measurements rely on the fact that the scattering intensity of solar UV (effective scattering height) changes with solar zenith angle (SZA). Since most of the ozone in the atmospheric column is in the stratosphere, the information content of the tropospheric part of the retrieval is limited, and only ~5 0% or less of the information in layer 1 (1000-250 hPa in the standard retrieval) comes from the troposphere (Stone et al, 2015; Text S-9), while the rest of the information comes from the adjacent stratospheric layers.…”
Section: Umkehrmentioning
confidence: 99%
“…Zenith-sky Umkehr retrievals from Dobson instruments that have historically been processed with the algorithm developed by Mateer and DeLuisi (1992) used TOCdependent a priori profiles to constrain the retrieval. While this practice can lead to artefacts when calculating trends (Petropavlovskikh et al, 2005;Stone et al, 2015), the approach may be the best choice if a profile with the smallest uncertainty possible is sought for a specific purpose.…”
Section: Discussionmentioning
confidence: 99%
“…A value of d s = 3.0 may seem low, but it is consistent with values of d s resulting from the standard zenith-sky Umkehr technique. For example, Stone et al (2015) reported a value of d s = 3.1 for Dobson zenithsky Umkehr retrievals using the Dobson C wavelength pair (311.4 and 332.4 nm) and the standard Dobson SZAs ranging from 60 to 90 • .…”
Section: Comparison With Balloon-sonde and Mls Profiles -Statisticsmentioning
confidence: 99%